2004
DOI: 10.1196/annals.1331.023
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Vitamin E Cancer Prevention Trial

Abstract: Preclinical, epidemiological, and phase III data from randomized, placebo-controlled clinical trials suggest that both selenium and vitamin E have potential efficacy in prostate cancer prevention. In vitro evidence suggests that selenium and vitamin E work synergistically to cause cell-cycle arrest, induce caspase-mediated apoptosis, and act as antiandrogens in arresting clonal expansion of nascent tumors. The Selenium and Vitamin E Cancer Prevention Trial (SELECT), sponsored by the National Cancer Institute, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 29 publications
1
27
0
1
Order By: Relevance
“…However, we cannot exclude the possibility of confounding that may have influenced our results. The SELCT trial is an ongoing randomized trial designed to answer whether selenium and vitamin E prevent the risk of prostate cancer [30]. Until the publication of the results of this trial, we do not advise clinicians prescribe selenium for prostate cancer prevention.…”
Section: Discussionmentioning
confidence: 96%
“…However, we cannot exclude the possibility of confounding that may have influenced our results. The SELCT trial is an ongoing randomized trial designed to answer whether selenium and vitamin E prevent the risk of prostate cancer [30]. Until the publication of the results of this trial, we do not advise clinicians prescribe selenium for prostate cancer prevention.…”
Section: Discussionmentioning
confidence: 96%
“…The results indicated that daily supplementation with selenium-enriched yeast (200 lg/day) caused a 63% reduction in prostate cancer, 58% reduction in colorectal cancer, and 46% reduction of lung cancer [214]. However, the Selenium and Vitamin E Cancer Prevention Trial (SELECT) trial investigated the chemopreventive effects of selenium and vitamin E on prostate cancer in 32,400 men and found no effect [158,215]. The Third National Health and Nutrition Examination Survey conducted by Bleys et al measured the selenium serum concentration in 13,887 adults and determined that increasing selenium levels were associated with a decrease in deaths due to cancer [216].…”
Section: Cellular and In Vivo Studiesmentioning
confidence: 94%
“…Cardiomyopathy and rhabdomylosis are characteristics of selenium deficiency (37). Recently, supplementation with selenium has been positively correlated with lowered incidences in prostate cancer and HIV replication, where macrophage activation is a crucial step in the inflammatory processes that form the underlying basis of disease progression (38). Here we show that selenium supplementation of macrophages downregulates the expression of COX-2, via the inhibition of the enzymatic activity of IKK␤ by covalent modification of an essential Cys residue within its activation loop by 15d-PGJ 2 .…”
Section: Discussionmentioning
confidence: 99%